Challenges and Strategies using Application in Online Teaching during Pandemic - Fransiska M. Ena Tukan (English Education : English Journal for Teaching and Learning, 2020)
This study aims to explain (1) the teacher’s challenges using the application in online teaching classroom during the COVID-19 pandemic, and (2) the strategies used by teachers in teaching using the application. The participants of the research were the English teachers at SMA/SMK/MA in Yogyakarta, Gunungkidul, Magelang, and Kebumen. A qualitative method was employed in this research and using interviews via WhatsApp as a data collection technique. The findings showed that teachers had the challenges such as (1) operating the application during online learning, (2) developing the material, assessment, and evaluation in teaching, (3) developing the teaching method, (4) combining the material and application, and (5) motivating the students and parents. The strategies used by the teacher when using the application in teaching such as (1) watching the video tutorial, (2) choosing a  suitable application for teaching, (3) arranging the new learning schedule, (4) developing the creativity in designing the material, and (5) giving the simple material and task for the students.